The Family in Past Perspective 2021
DOI: 10.4324/9780429355912-10
|View full text |Cite
|
Sign up to set email alerts
|

We’re all in this together: accessing the maternal-infant relationship in prehistoric Vietnam

Abstract: Family can be broadly defined as a community of care, cooperation and shared resources. As we move further into the past, however, our ability to observe these relationships becomes blurred.For most of human history, ethnographic and historical documents are lacking; identity and relationships are therefore inferred through the analyses of mortuary practices and evidence of production through artefacts and features. In this study, we examine the unique connection that exists between mother and infant, illustra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
3
1
0
Order By: Relevance
“…As such, the perinates reported here are proxies for very poor maternal health at Man Bac. These findings are supported by Adams et al (2021) who reported multiple episodes of in utero stress via nitrogen isotopes and deciduous linear enamel hypoplasia in the Man Bac infants. Adams et al (2021) report a case of a 3‐year‐old at time of death who exhibited greater catabolism (higher δ 15 N levels) due to stress in utero than after birth, a rare but important finding in the context of infant and maternal health during the Neolithic period of northern Vietnam.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…As such, the perinates reported here are proxies for very poor maternal health at Man Bac. These findings are supported by Adams et al (2021) who reported multiple episodes of in utero stress via nitrogen isotopes and deciduous linear enamel hypoplasia in the Man Bac infants. Adams et al (2021) report a case of a 3‐year‐old at time of death who exhibited greater catabolism (higher δ 15 N levels) due to stress in utero than after birth, a rare but important finding in the context of infant and maternal health during the Neolithic period of northern Vietnam.…”
Section: Discussionsupporting
confidence: 76%
“…Infection also appears to peak in the second trimester, although the dearth of data on infection in the first trimester is likely biasing this pattern (Desai et al, 2007; Takem & D'Alessandro, 2013). Kendall et al (2020) demonstrated that higher δ 15 N and lower δ 13 C values were present in babies during the late fetal period, a similar finding to Adams et al (2021). Kendall et al (2020) interpreted this as due to higher inflammation during malarial infection inhibiting transfer of nutrients to the fetus.…”
Section: Discussionsupporting
confidence: 52%
“…Substantial evidence for the established presence of treponemal disease in this region from before the agricultural transition exists and this, among a suite of other infections invisible in the archeological record, may have reduced the bioavailable vitamin D, and other vitamins and minerals in this infant's gut. Respiratory disease as evident in eight Adams et al, 2021;Snoddy et al, 2017Snoddy, Beaumont, et al, 2020;Vlok et al, 2020Vlok et al, , 2021, the rachitic endochondral porosity appears, heavier and coarser in morphology than what we have observed in scorbutic endochondral porosity.…”
Section: A Case Study From the Atacama Desertsupporting
confidence: 41%
“…The population was under some demographic stress with a high fertility rate of 6.8 births per woman as well as an estimated elevated rate of natural population increase of 4.3% per annum . Furthermore, extreme physiological stress and poor health were evidenced by treponemal disease, malaria, thalassaemia, anaemia and scurvy identified in both adults and children (Adams et al, 2021;McDonell & Oxenham, 2014;Vlok et al, 2020;2021a;2021b). Walker et al (2022a) recently examined humeral and femoral bone histology in an individual from Mán Bạc afflicted with paraplegia (possibly quadriplegia), describing microscopic changes in skeletal tissue in response to muscular dysfunction.…”
Section: Methodsmentioning
confidence: 99%